Digital Inequality and Digital Entrepreneurship in Indonesia - Irawan, Andri; Yendra, Yendra; Sutisna, Entis; Marihi, Laode; Mardatillah, Mardatillah; Soelistya, Djoko (Universitas Brawijaya, Indonesia, 2024)
In the era of disruption, myriads of digital entrepreneur in Indonesia still faces significant problems due to the demographical disadvantage and the lack of government policies that can overcome the problem faced. This series of problems has resulted to the existence of digital inequality. This study aimed to explains the digital inequality in Indonesia that has an impact on the inequality of opportunities and challenges for digital entrepreneurs. Qualitative approach to case studies in Indonesia. Informants were taken from 3 regions in Indonesia as well as government representatives responsible for the development of information and communication technology. Data was collected through in-depth interviews online and data was processed with the help of NVivo12. The study was conducted for 6 months. The results of this research will certainly have implications for the development of technology research, digitalization and communication as well as business. If the problem of digital inequality is resolved, digital business development in Indonesia will be more competitive. However, the biggest implication can certainly be a recommendation for information and communication technology development policies in Indonesia, such as the policy of building base transceiver station (BTS) in areas where there is no internet connectivity.